CONTENT OF GROSS PROTEIN, FIBER IN NEUTRAL DETERGENT, PRODUCTION OF AERIAL AND ROOT DRY MATTER OF MARANDU GRASS AND MOMBAÇA GRASS UNDER THE EFFECT OF DIFFERENT DOSES OF HUMIC SUBSTANCES: TEOR DE PROTEINA BRUTA, FIBRA EM DETERGENTE NEUTRO, PRODUÇÃO DE MATÉRIA SECA AÉREA E RADICULAR DO CAPIM MARANDU E CAPIM MOMBAÇA SOB EFEITO DE DIFERENTES DOSES SUBSTÂNCIAS HÚMICAS - Deminicis, Bruno Borges; Deminicis, Renata Gomes da Silveira; Dobbss, Leonardo Barros; Lista, Fábio Nunes (Scientia Agraria Paranaensis, 2022)
Humic substances (HS), composed of humic acids, fulvic acids and humin, are the main components of soil organic matter and originate from biochemical transformations of compounds such as lignin, cellulose, hemicellulose, sugars, amino acids, etc. The effects of humic substances in plants are related to the increase in the absorption of nutrients, due to the influence on the permeability of the cell membrane and the chelating power, as well as photosynthesis, the formation of ATP, amino acids and proteins. Humic substances directly alter the biochemical metabolism of plants and, consequently, can influence their growth and development. However, studies on the use of SH in forage plants and pastures are scarce. In order to optimize the use of humic substances for tropical grasses, it was carried out in pots in a greenhouse. Humic substances were extracted from vermicompost, according to the International Society of Humic Substances (ISHS). For the application of humic substances, a humic solution was produced by diluting the concentrated solution in water at concentrations of (0; 12.5; 25 and 50%), and the solution was applied with a sprayer/hand sprayer (300mL). The experimental design used was completely randomized in a 2 x 4 factorial scheme (two forages, four SH doses), with 5 replications. At 45 days, the plants were cut, separating them into shoots and roots. The samples were removed from the oven for determination of dry matter, crude protein and NDF. The leaves and roots of the samples were, after weighing (for green matter) and before drying, digitalized to determine leaf area and leaf area index. The results were submitted to analysis of variance and regression at a 5% level using the "F" test. The estimates of the regression parameters were evaluated by the "t" test at a 5% significance level. The objective was to evaluate the leaf area, shoot and root yield of Brachiaria brizantha (Syn Urochloa brizantha), cv. Marandu and Panicum maximum (Syn Megathyrsus maximus) cv. Mombasa subjected to different doses of humic substances. The best doses of humic substances verified in the present study, for better yield of the shoot and root, were 50% for cv. Mombasa and 25% for cv. Marandu.